Inhaled Microplastics as Emerging Respiratory Toxicants: From Cellular Mechanisms to Global Health Policy - Farhanah Edora Mohamed Kasturi; Beevenna Kaur Darmindar Singh; Suresh Kumar; Muhammad Danial Che Ramli (Microplastics, 2026)
Background: Airborne microplastics (AMPs) are an emerging air pollutant and there are growing concerns about their potential effects on respiratory health due to their persistence, inhalability and ability to carry other toxic pollutants. Methods: Relevant peer-reviewed studies released from 2015 to 2025 were located by searches on PubMed, Scopus, and Web of Science. Data from experimental, epidemiological, and review research were amalgamated to investigate sources of airborne microplastics, routes of exposure, analytical methodologies, respiratory toxicological processes, and regulatory viewpoints. Results: Modern studies suggest inhaled antimicrobic peptides can reach the lower respiratory tract and cause chronic pulmonary inflammation via induction of oxidative stress, mitochondrial dysfunction, epithelial barrier damage, inflammasome activation, immune system imbalance and extracellular matrix remodeling. These pathways have been associated with chronic respiratory diseases, such as chronic obstructive pulmonary disease, asthma, pulmonary fibrosis, and lung carcinoma. Toxicity can be increased by the accumulation of heavy metals, persistent organic pollutants and microbiological impurities. However, the lack of standardised protocols for exposure assessment, inconsistency of sampling and analytical methods and limited human epidemiological data hamper health risk assessment. Conclusions: Airborne microplastics are an emerging environmental health concern with potentially significant effects on respiratory health. Harmonised surveillance strategies, standardised analytical methods, improved inhalation exposure models and prolonged epidemiological studies are urgently needed to improve risk assessment and enable evidence-based air quality policy for the protection of respiratory health.